2007
DOI: 10.1007/s11211-007-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Are “We” More Punitive than “Me”? Self-Construal Styles, Justice-Related Attitudes, and Punitive Judgments

Abstract: Cross-cultural as well as procedural justice research suggests that an interdependent self-construal is connected to more justice-related concerns, more moral outrage following observed unethical behavior, and a preference for effective but constructive sanctions. Independent self-construal, on the other hand, is expected to be connected to weaker moral reactions toward injustice, but also to preferring punitive over constructive forms of sanctions. Two studies were conducted in which dispositional self-constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 53 publications
3
19
0
Order By: Relevance
“…The present findings are consistent with previous findings in which a sense of connectedness with others increased a concern for justice when observing social transgressions (e.g., Correia et al, 2007;Gollwitzer & Bücklein, 2007;Kerr et al, 1995;Novak & Lerner, 1968;Van Prooijen, 2006;Van Prooijen & Lam, 2007). This is not to say, however, that all forms of connectedness to others increase a concern for justice in all possible situations.…”
Section: Discussionsupporting
confidence: 92%
“…The present findings are consistent with previous findings in which a sense of connectedness with others increased a concern for justice when observing social transgressions (e.g., Correia et al, 2007;Gollwitzer & Bücklein, 2007;Kerr et al, 1995;Novak & Lerner, 1968;Van Prooijen, 2006;Van Prooijen & Lam, 2007). This is not to say, however, that all forms of connectedness to others increase a concern for justice in all possible situations.…”
Section: Discussionsupporting
confidence: 92%
“…An alternative explanation can be provided by differences in socialization that remain even after the reunification and that may be reflected by the higher degree of interdependence that has been reported among East compared to West Germans. As research has shown, interdependence tends to be positively correlated with justice sensitivity (Gollwitzer & Bücklein, 2007).…”
Section: Perpetratormentioning
confidence: 98%
“…Such a setup thus mimics lay people's responses to the injustices that they perceive on a day‐to‐day basis through modern media. One set of studies reveals that activation of the social self increases desire to punish the offender . Thus, whereas activating an individualistic mindset makes people more sensitive to personally experienced injustice, activation of a social mindset makes people more sensitive to injustice experienced by others.…”
Section: Social Motives For Justice Judgmentsmentioning
confidence: 99%
“…One set of studies reveals that activation of the social self increases desire to punish the offender. 28 Thus, whereas activating an individualistic mindset makes people more sensitive to personally experienced injustice, 21 activation of a social mindset makes people more sensitive to injustice experienced by others. Additional findings reveal that activation of the social self also shapes justice-based reactions to crime victims.…”
Section: Social Motives For Justice Judgmentsmentioning
confidence: 99%